The HLA‐A*33:110 allele identified in a volunteer donor for hematopoietic stem cell transplant. (25th September 2018) - Baek, I.‐C.; Choi, E.‐J.; Shin, D.‐H.; Kim, H.‐J.; Kim, T.‐G.
Abstract : HLA‐A*33:110 differs from HLA‐A*33:03:01:01 in a codon 149 in exon 3.